The evaluation of a positive psychology-based intervention in enhancing self-esteem among Malaysian preschool children - Aminuddin, Aisyah Nabilah; Hussaini Dzulkeflee, Amanina; Azwani Zam, Arissa Irena; Zahra Mohamad Yusra, Fateemah Az-Zahra; Ismail, Nur Adibah; Mohd Rasid, Nur Insyirah Asyura; Lukman, Nur Wahidah; Lourdunathan, Pamilia (IIUM Press, 2025)
This exploratory-sequential study examined challenges related to positive psychology among kindergarten children and developed an intervention to address them. A needs analysis, conducted through interviews and observations with five teachers and 11 kindergarteners, identified self-esteem as a key concern. Insights from thematic analysis guided the design of a play-based intervention rooted in positive psychology principles, including activities such as Laughter Yoga, Guess the Voice, and Group Drawing to improve emotional well-being and self-confidence. Pre- and post-intervention mood trackers evaluated changes in the children’s emotional states. Both quantitative and qualitative results suggest a potential positive impact of play-based interventions on self-esteem among preschoolers. While play activities may not directly build self-esteem, they significantly contribute to creating a supportive environment. However, the study's brief intervention period and lack of standardised assessment tools limit the wider applicability of the findings. Acknowledging these limitations, the paper emphasises its promising preliminary results for future research. Subsequent studies should involve longer interventions and validated assessment instruments for a more comprehensive evaluation of outcomes